Empirical components of firm export market performance in Uganda: structural equation modelling (SEM) approach - Haque, A. K. M. Ahasanul; Is’haq, Amandu Yassin (American University in the Emirates, 2016)
Firm export performance (FEP) is important to both the firm and national economy. This makes it imperative to identify its determinants to appropriately manage the implications. Therefore, the purpose of this paper is to empirically identify the determinants FEP. Quantitative cross-sectional survey was conducted. Self-administered questionnaires were used to collect data from 250 firm export managers from selected industries in the export sector in Uganda. Psychometric analyses covering descriptive statistics of the scale items, reliability, exploratory, confirmatory, and validities analyses were performed. Finally, structural equation modelling was used to analyse the hypothesised relationships and validate the FEP model. The results identified and confirmed FEP determinants to include export market orientation, export market environment and organisational learning have indirect relationship with FEP. It also identified export market information system, export market strategy and organisational innovations capability as mediating variables. This implies that an export development strategy needs to invest in implementation and practice of these predictors. Appropriate implementation and practice of these variables would create competitive edge hence improving FEP. This would consequently enable the firms to realise their export objectives. From the indication of available literature, it is not clear what determines acceptable level of FEP. The literature further indicates that knowledge on FEP is fragmented, contradictory, and full of controversies, lacking consensus and the theory is still at infancy stage of development. Export corporations are reportedly facing challenges in operationalising their export objectives, leading to continued poor performance. Yet, not much of the little FEP comes from developing world especially Africa. Therefore, this study attempts to bridge this gap in literature from African perspective. In conclusion, FEP is determined by export market orientation, export market environment and organisational learning. These determinants yield better influence through export market information system, export market strategy and organisational innovations capability. Therefore, firm management could realise better export performance by taking into appropriate practice of these identified determinant variables. This would consequently enable the firm to achieve its strategic growth objective that translates better national economy.